2021
DOI: 10.1111/vru.13039
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the collapsed cone convolution and Monte Carlo algorithms for radiation therapy planning of canine sinonasal tumors reveals significant dosimetric differences

Abstract: Computer‐based radiation therapy requires high targeting and dosimetric precision. Analytical dosimetric algorithms typically are fast and clinically viable but can have increasing errors near air‐bone interfaces. These are commonly found within dogs undergoing radiation planning for sinonasal cancer. This retrospective methods comparison study is designed to compare the dosimetry of both tumor volumes and organs at risk and quantify the differences between collapsed cone convolution (CCC) and Monte Carlo (MC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[ 28 ] and Lee et al . [ 29 ] indicated that the CC dose overestimated the 3% dose in the bone region compared with the PMC dose. Therefore, Type B (superposition/convolution) algorithms would overestimate dose distributions more than Type C algorithms, as indicated in previously published studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 28 ] and Lee et al . [ 29 ] indicated that the CC dose overestimated the 3% dose in the bone region compared with the PMC dose. Therefore, Type B (superposition/convolution) algorithms would overestimate dose distributions more than Type C algorithms, as indicated in previously published studies.…”
Section: Discussionmentioning
confidence: 99%
“…The dose difference in the Type B algorithm can increase as a function of the HU value range compared with the Type C algorithm. AAA and CC are calculated using dose-to-water, while AXB and PMC are calculated using dose-to-medium [ 29 ]. Differences in the method that take into account the material density will likely lead to systematic errors with increases in the HU values as different calculation methods produce different results.…”
Section: Discussionmentioning
confidence: 99%